Coerência, convergência e cooperaç\~ao regulatória nos capítulos de barreiras técnicas ao comércio e medidas sanitárias e fitossanitárias do acordo transpacífico - Vera Thorstensen; Alebe Mesquita (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This article aims to develop an analysis of the regulatory coherence of theme related to technical barriers to trade (TBT) and sanitary and phytosanitary measures (SPS) of the Trans-Pacific Partnership Agreement (TPP). The work outlines the rights and obligations of those most relevant chapters, its main innovations, their relationship with the WTO agreements, and that it is subject to the dispute settlement system of both the TPP as the WTO.
Keywords: F13; F53; F10; 330; TPP; international trade; TBT; SPS; WTO